Island hopping for cells - Schwarz, Ulrich S. (Nature physics, 2019)
A two-state hopping experiment combined with a dynamical systems model reveals that cancer cells are deterministically driven across barriers, whereas normal cells cross only with the help of stochastic fluctuations.
Gesehen am 28.08.2019